How Jokowi communicates with the public during Covid-19 crisis: an analysis of tweets on Twitter - Prayoga, Kadhung (Penerbit Universiti Kebangsaan Malaysia, 2020)
The coronavirus pandemic has caused mass fear and panic in Indonesia. Irrational behaviour is carried out by people ranging from panic buying to violating the government appeals and rules. This condition certainly leads to the importance of disaster communication carried out by an opinion leader. Therefore, the objective of writing this paper is to analyse how the disaster communication was carried out by Jokowi on Twitter during the Covid-19 pandemic. This research was conducted using data from President Jokowi’s tweets (@jokowi) related to Covid-19 from January 1, 2020, to April 30, 2020. The number of tweets analysed was 150 tweets related to coronavirus from a total of 290 tweets. These tweets were collected automatically with the help of the Ncapture and NVIVO 12 analysis tools. However, the researcher also re-checked the data manually. The collected data is then encoded using Microsoft Excel. Finally, the data was analysed using quantitative content analysis. The results found that Jokowi has provided a wide variety of information, ranging from socialising policies related to the handling of COVID-19 in Indonesia to the extension of condolences to the affected patients. The use of photos and videos is also carried out by Jokowi to increase public awareness. Unfortunately, disaster communications were not carried out in advance before the pandemic occurred. It was only actively carried out when the pandemic had claimed many victims. Furthermore, coordination with many parties in providing the information is also crucial. Finally, Jokowi should use a hashtag (#) more often to reach a wider range of tweets.